Empirical Development of the Best Practices of Coaching and Mentoring for High Performance of Competency-based Education - Takei , Hideki; Anthony, Peter; Fountain, Elizabeth; Williams, Luke (International Research in Education, 2022)
Competency-based education (CBE) is different from traditional classroom instruction. For CBE, organizing faculty development programs has been a mandatory requirement for higher education institutions to offer quality CBE. The programs’ main goal is to make their faculty members effective coaches or mentors. Faculty development professionals in leading CBE higher education institutions have suggested developing the best coaching and mentoring practices to make faculty development programs more effective. This paper assessed and revised our current best practices to improve our faculty development programs to develop better versions of the best practices.